35.9k views
14 votes
1 - (2n + 9) = 4(1-2)

User Laky
by
5.0k points

2 Answers

9 votes

Answer:

n = -2

Explanation:

remove () from equation so its 1-2n-9=4× -1

calculate the differences and multiply

-8-2n=-4

move the constant to the right of the equation -2n=-4+8

calculate the sum -2n=4 divide both sides of equation by -2

and boom n=-2

User Puteri
by
4.9k points
6 votes

Answer:

n=-2

Explanation:

1−(2n+9)=4(1−2)

1+−1(2n+9)=4(1−2)

1+−1(2n)+(−1)(9)=4(1−2)

1+−2n+−9=4(1−2)

1+−2n+−9=−4

(−2n)+(1+−9)=−4

−2n+−8=−4

−2n−8=−4

−2n−8+8=−4+8

−2n=4

Divide both sides by -2

-2n/2=4/-2

n=-2

User Tadasajon
by
4.3k points